2021
DOI: 10.3390/ph14050401
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology, Physiology and Genetics of the Neuropeptide S System

Abstract: The Neuropeptide S (NPS) system is a rather ‘young’ transmitter system that was discovered and functionally described less than 20 years ago. This review highlights the progress that has been made in elucidating its pharmacology, anatomical distribution, and functional involvement in a variety of physiological effects, including behavior and immune functions. Early on, genetic variations of the human NPS receptor (NPSR1) have attracted attention and we summarize current hypotheses of genetic linkage with disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 119 publications
0
7
0
Order By: Relevance
“…The NPS which acts as the coordinator of the HPA axis ( 57 ), also engages in the regulatory interaction of social functioning. NPS, as part of the excitatory signaling system, is responsible for many functions, including initiation of arousal and regulation of wakefulness ( 12 , 20 , 58 ), reduction of anxiety ( 12 , 20 , 58 , 59 ), promotion of learning and memory enhancement ( 23 , 49 ), reduction of psychotic functioning ( 58 ), regulation of food intake ( 12 , 58 ), and stimulation of stress hormone release ( 12 , 20 , 60 , 84 ). Neuropeptide Y (NPY) is a pancreatic peptide and is one of the most important molecules in the autonomic, central, and peripheral nervous system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NPS which acts as the coordinator of the HPA axis ( 57 ), also engages in the regulatory interaction of social functioning. NPS, as part of the excitatory signaling system, is responsible for many functions, including initiation of arousal and regulation of wakefulness ( 12 , 20 , 58 ), reduction of anxiety ( 12 , 20 , 58 , 59 ), promotion of learning and memory enhancement ( 23 , 49 ), reduction of psychotic functioning ( 58 ), regulation of food intake ( 12 , 58 ), and stimulation of stress hormone release ( 12 , 20 , 60 , 84 ). Neuropeptide Y (NPY) is a pancreatic peptide and is one of the most important molecules in the autonomic, central, and peripheral nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of NPS in the brain is uneven. The studies on rat and mice revealed that the NPS precursors mRNA is strongly expressed in hypothalamus, thalamus, hippocampal formation, and para-hippocampal regions ( 20 ). NPS-expressing neurons are presented most abundantly within the cell populations located close to the locus coeruleus, and sensory and caudate nuclei ( 13 ).…”
Section: Anatomical Distribution Of Nps and Its Biochemical Propertiesmentioning
confidence: 99%
“…Neuropeptide S (NPS), as a product of 89-aminoacid propeptide conversion, is a ligand of G-coupled receptor (NPSR) formerly known as GPR 154 [6]. NPSR stimulation increases cAMP level and probably phosphorylates protein kinase MAPK that result in the activation of nerve cell [7].…”
Section: Introductionmentioning
confidence: 99%
“…Against this background, newly identified modulators of stress responses neuromedin U (NMU) and neuropeptide S (NPS) seem to be specifically worth investigating. Neuropeptide S (NPS), as a product of 89-amino acid propeptide conversion, is a ligand of the G-coupled receptor (NPSR) formerly known as GPR 154 [ 15 ]. NPSR stimulation causes calcium release to the neuroplasm, increases cAMP levels, and probably phosphorylates protein kinase MAPK resulting in the activation of neurons [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The NPS receptor is in turn widely distributed in the rat brain, especially in the hypothalamus, amygdala, hippocampus, olfactory bulb, as well as in some thalamic and cortical regions [ 20 ]. NPS is a neuromodulator with a wide spectrum of regulatory activity in the brain; it exposes anxiolytic action, stabilizes wakefulness, regulates food intake, and plays a role in the mechanisms of addiction [ 15 , 21 , 22 ]. From a neuropsychiatric viewpoint, an anchoring of NPS in the fear-related neural pathways seem to be particularly important.…”
Section: Introductionmentioning
confidence: 99%